Recurrent Hyponatremia as Presenting Manifestation of Pituitary Macroadenoma - Rajput R. (Sciendo, 2017)
Hyponatremia is commonly seen electrolyte disturbance clinically. It is potentially life-threatening and requires prompt diagnosis and treatment. Non-functioning pituitary macroadenoma generally presents with a headache, visual disturbances, and the diagnosis is often delayed because of nonspecific nature of symptoms. Hyponatremia being initial manifestation before other common symptoms of pituitary macroadenoma is rare. We present a case of 55-year-old male with recurrent episodes of hyponatremia who was found to non-functioning pituitary macroadenoma along with panhypopituitarism. He was managed with hormone replacements. Our case highlights the importance of correct diagnosis of hyponatremia, measurement of the thyroid, adrenal and pituitary function in cases of hyponatremia.